Les adolescentes membres des bandes marginales : un potentiel antisocial atténué par la dynamique de la bande ? - Lanctôt, Nadine; LeBlanc, Marc (Criminologie, 1997)
The goal of this article is to improve our knowledge concerning the social and personal characteristics of the female gang members. Data have been collected from 150 girls who were convicted by the juvenile court of Montreal during 1992 and 1993. The analysis shows that girls who join gangs have serious handicaps which are related to their social adaptation, their personality and their deviant and delinquent conducts. Consequently, female gang membership responds to a selection process, as it does with the male membership. The profile of the female also changes depending on the structure of the gang to which they join. As the gang becomes more organized, the girls' personality gets worst. However, the context of the organized gangs seems to limit the girls to auxiliary roles rather then being an opportunity to discharge their antisocial potential.